ANALYSIS OF THE APPLICATION OF MEDIA CONVERGENCE IN RADIO BROADCASTING BUSINESSES IN PONOROGO - Nur Aini Shofiya Asy'ari; Mohammad Luthfi (Universitas Muhammadiyah Jakarta, 2019)
The development of new media in recent years has forced the mainstream media industry to transform following the information consumption pattern of people who have switched using new media. Especially radio whose lis- tenership trend is decreasing from year to year. In 2015 radio listenership was only around 14% and continued to decline to 11% in 2016. People are currently chooses gadgets as an information media, the internet and social media are the most important parts of society. Realizing this phenomenon, the mainstream media industry, espe- cially radio stations, synergized with new media. Making radio station applications on gadgets, creating website portals, streaming radio, video streaming and social media accounts, a step or strategy known as media conver- gence. The media convergence strategy is also applied by radio stations in Ponorogo. Almost all radio stations in Ponorogo have implemented media convergence. But to know whether this step is effective to attract the attention of the audience to have an impact on listenership and the rise of the radio media industry needs further research. This study aims to find out how media convergence is applied by radios in Ponorogo and how media convergence helps the development of radio in Ponorogo. By using a qualitative approach, this study analyzes the data previously obtained from field survey activities and interviews about the implementation of radio-radio media conver- gence in Ponorogo then studied with theoretical studies of Communication Science and Media Convergence. The results showed that from 6 private radio stations in Ponorogo, 5 radios have converged media by using almost all forms of new media, but not accompanied by a good level of understanding of what media convergence is so that the convergence step does not reach the desired target. The convergence strategy carried out by radio stations in Ponorogo is carried out only by following existing developments without any standard formulation in its imple- mentation. Keywords: Convergence, New Media, Radio in Ponorogo